Multistation Whole-Body High-Spatial-Resolution MR Angiography Using a 32-Channel MR System - Nael, Kambiz; Ruehm, Stefan G; Michaely, Henrik J; Saleh, Roya; Lee, Margaret; Laub, Gerhard; Finn, J. Paul (American journal of roentgenology (1976), 2007)
The objective of our study was to investigate a multistation whole-body MR angiography (MRA) protocol using a 32-channel MR system with multicoil technology in a population of patients with suspected peripheral vascular disease (PVD). Fifty consecutive patients with suspected PVD (31 men, 19 women; age range, 46-91 years) underwent multistation whole-body contrast-enhanced MR angiography (CE-MRA) on a 32-channel 1.5-T MR system equipped with multicoil technology. A two-step contrast injection protocol was used: After the first injection, images of the most proximal station (station I, head and neck) were acquired, followed by the most distal station (station IV, calves). Images of the intermediate two stations (station II, chest and abdomen; station III, pelvis and thighs) were acquired during the second injection. Conventional catheter angiography was performed for symptomatic vascular regions in 30 patients. The image quality of the arterial segments and the presence and degree of the arterial stenosis were evaluated by two radiologists. The interobserver variability was calculated by kappa statistics, and comparative analysis between CE-MRA and catheter angiography was performed by means of the Spearman's rank correlation coefficient. Most of the vascular segments (1,912/1,976 [97%]) were visualized on wholebody CE-MRA with diagnostic image quality. Significant arterial disease (> or = 50%) was detected in 167 (observer 1) and 177 (observer 2) segments with excellent interobserver agreement (kappa = 0.84). There was a significant correlation between CE-MRA and conventional angiography for the degree of stenosis (R = 0.92 and 0.89 for observers 1 and 2, respectively). The sensitivity and specificity of CE-MRA for the detection of arterial stenoses 50% or greater were 92% and 96% for observer 1 and 93% and 97% for observer 2, respectively, compared with those of conventional angiography. Using a multichannel radiofrequency system with multicoil technology, the whole-body CE-MRA approach outlined in this article is able to provide high-spatial-resolution data sets with high diagnostic image quality for evaluation of arterial occlusive disease in most vascular territories.